NURSING PROCESS: A PROPOSAL OF TEACHING THROUGH THE PROBLEM-BASED LEARNING. - Adélia Yaeko Kiosen Nakatani (Universidade Federal de Goias, 2002)
The way that teaching has been organized at the schools can represent na obstacle for the acquisition of theabilities to think, to reflect and to make decisions, influencing the coping with practical problems during the NursingProcess. The goal of the present study is to analyze the implementation of a proposal of teaching Nursing Processthrough the Problematical method, particularly through the Arch Method. This is an action-research project,developed at the Nursing School of the Federal University of Goiás, during 1998 and 1999. The subjects weresecond year students of Nursing, attending the course Methodology of Nursing Assistence. To collect the data weuse activity and self-evaluation reports from students, field data and instruments of cognitive, affective andpsychomotor evaluation. The evaluation of the reports was done following the established guidelines for teaching ineach phase, and most of the scores obtained were medium to high (3 to 5), with the exception of the nursingassistance phase evaluation, with scores between 1 and 2. In the affective evaluation the majority of the studentsmentioned that the implementation of the nursing process phases, does not happen as the literature suggests, andmanifested the importance of the Nursing Process to improve the quality of assistance and the desire of use itduring the professional practical. The psychomotor evaluation was performed through physical lunge exam and theimplementation of technical procedures. More than 50% of the students had scores between 4 and 5 in the items ofinspection and auscultation, presenting difficulties to perform the abilities of palpation and percussion. The scoreobtained in the evaluation of procedures implementation ranged from 4 to 5. The cognitive evaluation of theNursing Process phases was realized through a write test with mean grades between 33,4 and 51,4, with amaximum of 100 points. The differences between written evaluation and reports may be due to the type of domainmeasured and/or the strategy of the evaluation. The guidelines made for teaching, the strategies for teaching andfor evaluation, the facilities and difficulties and perceptions pointed out by the research participants in relation to thethematic may be useful to trigger discussions about teaching the Nursing Process. Although we cannot extend theresults of these experiences to others groups, we expect this investigation to be a contribution for professionalsand professors that want to adopt the Problem-based Learning, triggering discussions about the pedagogic project.